Corporate audit theory - Lee, T. A. (Thomas Alexander) (London ; New York : Chapman & Hall, 1993)
This book is about: The what and why of corporate audit theory; Doubt, verification and corporate auditing; Economic and social roles for corporate auditing;...
Keywords: Economics; Corporations; Auditing; Corporations -- Auditing